Performance improvement of wind‐driven self‐excited induction generator using fuzzy logic controller. (20th June 2019) - Dewangan, Sanjay; Dyanamina, Giribabu; Kumar, Navin
Summary: In this paper, an indirect vector control (IVC) technique for the stand‐alone self‐excited induction generator (SASEIG)‐based wind energy conversion system (WECS) is proposed to independently control torque, active power, reactive power, and DC voltage for variable wind speed operation without fault and constant wind speed operation with single line‐to‐ground (LG) fault condition. This independent control of the WECS is obtained by using two‐level back to back converter, ie, machine side converter (MSC) and load side converter (LSC). To improve the dynamic response of the system during wind speed changes and fault operation, the PI controller in IVC is replaced with fuzzy logic controller (FLC). IVC of SEIG‐based WECS has been simulated in MATLAB/SIMULINK software, and prototype model of the proposed WECS is designed to experimentally validate the performance using dSPACE DS‐1104 R&D controller board. The results demonstrate that the performance of the proposed FLC‐based IVC controller is better than that the conventional PI controller–based IVC during variable speed and LG fault operations.